THE INFLUENCE OF RECEIVABLE TURNOVER RATE ON PROFITABILITY IN KARTIKA SARI KOTA BIMA WOMEN'S COOPERATIVE (KOPWAN) - ramadhani, rizky; Rimawan, M. (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This study aims to analyze the influence of accounts receivable turnover rates on profitability in the Kartika Sari Women's Cooperative (BOP). The population used is the financial statement data consisting of balance sheet data, and the calculation of business results (PHU) for 23 years and research samples for 5 years with the sampling used is purposive sampling with the criteria (1) financial statement data available for 5 consecutive years participated in 2014-2018 (2) 5-year sample data already represented existing population data for research needs. Data analysis techniques used are simple linear regression, simple correlation coefficient, coefficient of determination and hypothesis testing (t-2 party test). Based on the results of the analysis shows that the level of accounts receivable turnover does not significantly influence profitability in the Women's Cooperative (KOPWAN) Kartika Sari Kota Bima.